Robust multi‐rate modulation for cognitive radio communications over land mobile satellite channel at Ku‐band. (26th October 2016) - Murroni, Maurizio; Popescu, Vlad; Fadda, Mauro; Giusto, Daniele
Summary: The usable satellite spectrum is becoming scarce because of continuously increasing demand for broadcast, multimedia and interactive services. Because of the extensive use of predictive coding, multimedia data exhibit different sensitivities to transmission errors, which makes them suitable for unequal error protection (UEP) techniques. UEP mainly relies on differentiated error control coding which raises the robustness of data, but also increases the transmission bandwidth, which can be unwanted in case of limited resources often occurring in satellite communications. In this context, cognitive radio (CR) satellite communications has received important attention lately in the research community. In multi‐rate modulations (MRM), the properties of dy‐homogeneous signals are exploited to transmit over multiple band frequencies and time scales. MRM have been proved to be effective on unknown channels either in bandwidth or time. These conditions occur in CR networks where opportunistic communications are set up while preserving primaries licensed users. In CR, the uncertainty of transmission opportunity makes the use of error correcting codes not trivial. Therefore, to achieve robustness, this work proposes unequal power allocation (UPA) over the symbols of MRM according to both data sensitivity to channel errors and spectrum availability. As optimization criterion, the mean square error between the original and the decoded message, which has shown strong correlation with subjective perception, is used. To assess the effectiveness of the proposed scheme in realistic condition for CR satellite networks, the Land Mobile Satellite (LMS) model at Ku‐band is used to reproduce the memory associated with real channels. The non‐linearity of the satellite channel because of high power amplifier (HPA) prior to transmission has been accounted using the Saleh model. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The performance of MUPA applied to MRM for CR satellite networks is analyzed. Assuming perfect knowledge of the channel opportunities, different typical CR transmission scenarios have been considered by varying channel opportunity (i.e., B × T) availability from low to high busy channel. To reproduce the memory associated with the LMS channel, the two‐state Markov model has been used.